2020
DOI: 10.1021/acs.jpcc.0c07625
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Particle Material Properties on Electrostatic Liquid Marble Formation

Abstract: Specific particle material properties such as conductivity, cohesion, and density have been neither directly nor thoroughly studied regarding particle behavior in an electrostatic field and the follow-on impact this has on the electrostatic formation of liquid marbles. In this method, an applied electric field drives the extraction of particles from a bed and their transport to a pendent, earthed water droplet. Herein, prior studies of electrostatic formation of particle-stabilized droplets and liquid marbles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 30 publications
(60 reference statements)
1
37
0
Order By: Relevance
“…For example, previous work has clearly demonstrated that transferring unmodified glass resulted in net charge deposition 27 and is classified as conductive, while polystyrene particles transferred but did not deposit charge and are therefore deemed dielectric. 7,10 A similar interparticle repulsion has been reported in hydrophobic 3 μm diameter silanized silica microparticles at horizontal and vertical oil/water interfaces in the absence of an electric field. 28−31 These particles exhibited an interparticle spacing over nine times their diameter (up to 28 μm separation).…”
Section: ■ Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…For example, previous work has clearly demonstrated that transferring unmodified glass resulted in net charge deposition 27 and is classified as conductive, while polystyrene particles transferred but did not deposit charge and are therefore deemed dielectric. 7,10 A similar interparticle repulsion has been reported in hydrophobic 3 μm diameter silanized silica microparticles at horizontal and vertical oil/water interfaces in the absence of an electric field. 28−31 These particles exhibited an interparticle spacing over nine times their diameter (up to 28 μm separation).…”
Section: ■ Introductionsupporting
confidence: 68%
“…The slight increase in measured charge from the TCMS-coated glass and lycopodium was due to the induction of an image charge on the droplet as the drop-bed separation was reduced, thereby increasing the electric field strength and increasing the image charge. 8,10 The lack of measured charge transfer from the particles suggests that the transport of the particles for these samples was primarily due to dielectrophoresis (the induced motion of a neutral particle as a result of the polarization of the particle and gradient of a nonuniform electric field), and not due to a net charge on the particle. 10,49,50 This lack of charge is concordant with the observation of particle chains in the particle bed prior to, and on the droplet surface after, extraction and transfer due to the alignment of interparticle dipoles and interparticle electric field deformation in sets of particles (Figures 2 and 3 and Supporting Videos 1 and 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1.07 g cm −3 ) result in an increased mass per particle, which in turn leads to an expectation of a larger electrostatic force to extract them from the particle bed and transport them to the drop interface. 81 Surprisingly, for uncoated glass and PS particles, the separation distances for the initial particle extraction were similar, thus indicating particle extraction as a result of the competitive interaction of density, conductivity, and cohesion. The impact of density was further studied on particles of the same surface chemistry by coating PS and glass particles with increasingly conductive and cohesive PPy-Cl and PPy-dedoped coatings.…”
Section: Methodologies and Formation Under Electrostaticsmentioning
confidence: 89%
“…Spherical glass particles with a shape and size similar to those of PS latex particles but more than twice the density (2.31 g cm –3 , cf. 1.07 g cm –3 ) result in an increased mass per particle, which in turn leads to an expectation of a larger electrostatic force to extract them from the particle bed and transport them to the drop interface . Surprisingly, for uncoated glass and PS particles, the separation distances for the initial particle extraction were similar, thus indicating particle extraction as a result of the competitive interaction of density, conductivity, and cohesion.…”
Section: Liquid Marbles: Mechanism Composition Methodologies and Form...mentioning
confidence: 97%
“…This observation supports the idea that the interrelation Δ G het1 < Δ G het2 takes place, where Δ G het1 is the EBHN at the contact line and Δ G het2 is the EBHN at the saline/powder, respectively, regardless of the powder. In our future research, we plan to investigate an impact of electric field on interfacial crystallization taking place in Janus marbles …”
Section: Discussionmentioning
confidence: 99%